Plasma vitamin C levels in ESRD patients and occurrence of hypochromic erythrocytes. Issue 2 (12th September 2016) - Seibert, Eric; Richter, Anja; Kuhlmann, Martin K.; Wang, Suxin; Levin, Nathan W.; Kotanko, Peter; Handelman, Garry J.
Abstract: Introduction: The achievement of erythropoiesis in hemodialysis (HD) patients is typically managed with erythropoiesis‐stimulating‐agents (ESA's) and intravenous iron (IV‐iron). Using this treatment strategy, HD patients frequently show an elevated fraction of red blood cells (RBC) with hemoglobin (Hb) content per cell that is below the normal range, called hypochromic RBC. The low Hb content per RBC is the result of the clinical challenge of providing sufficient iron content to the bone marrow during erythropoiesis. Vitamin C supplements have been used to increase Hb levels in HD patients with refractory anemia, which supports the hypothesis that vitamin C mobilizes iron needed for Hb synthesis. Methods: We conducted a cross‐sectional survey in 149 prevalent HD patients of the percent hypochromic RBC, defined as RBC with Hb < 300 ng/uL of packed RBC, in relation to plasma vitamin C levels. We also measured high‐sensitivity CRP, (hs‐CRP), iron, and ferritin levels. and calculated ESA dose. Findings: High plasma levels of vitamin C were negatively associated with hypochromic RBC ( P < 0.003), and high ESA doses were positively associated ( P < 0.001). There was no significant association of hs‐CRP with percent hypochromic RBC. Discussion: This finding supports the hypothesis that vitamin C mobilizes iron stores, improves iron delivery to the bone marrow, and increase the fraction of RBC with normal Hb content. Further research is warranted on development of protocols for safe and effective use of supplemental vitamin C for management of renal anemia.